Intercultural Language Teaching: What Skills are needed to cope with a 21st Century EFL classroom? - BENMOUSSAT, Smail; BENMOUSAT, Nabil Djawad (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
The purpose of this article is to enrich EFL teachers’ understanding of the re-considerations involved in the nature of language learning with respect to the increasing process of global economic, political, linguistic and cultural integration. Needless to say, the globalization process tends to blur national boundaries, and this has already started with the European Union. What is more, the use of computer-assisted learning devices and other ICT tools, which have reduced the world into a village-like planet, have tremendously affected the field of foreign language pedagogy. All this, virtually creates a need for greater cross-cultural knowledge. The language learning communicative ends of the 70s and 80s have been re-moulded on intercultural grounds to give birth to a new concept: inter/cross-cultural competence. This intercultural scheme, one might argue, ensures the link between teaching language and learning culture, hence the intercultural language teaching or ‘teaching-and-learning language-and-culture’ approach (hereafter written TLLC), a term coined by Byram et al. (1994).